PERLINDUNGAN HUKUM TERHADAP KORBAN ATAS TINDAK PIDANA MALPRAKTEK DOKTER - Giatta Tarigan, Tri Reni Novita (NERACA KEADILAN, 2025)
Medical Malpractice is a medical action carried out by medical personnel that is not in accordance with the standard of action so that it harms the patient, this is categorized as negligence or intentional in criminal law. Medical malpractice according to the Great Dictionary of the Indonesian Language is the practice of medical practice that is carried out incorrectly or inappropriately in violation of the law or code of ethics. In general, malpractice is divided into two large groups, namely medical malpractice which usually also includes ethical malpractice and legal malpractice. While legal malpractice is divided into three, namely civil malpractice, criminal malpractice and administrative malpractice. The legal research conducted is normative legal research, namely research on legal norms based on literature, and conducting interviews with parties related to this research. Data analysis in this study was conducted qualitatively by connecting data obtained from the literature with legal norms related to criminal violations of medical malpractice. Based on the results of the research that has been conducted, it was concluded that the Tanah Karo Police prioritize the resolution of actions outside the court with a win-win solution by bringing together victims with perpetrators of malpractice. The obstacles faced by Tanah Karo Police Investigators in resolving malpractice include, lack of technical medical knowledge, dependence on expert testimony, and the difficulty of proving the element of error.